Evaluation of the endoscopic and surgical methods of prehepatic portal hypertension treatment in children - О.S. Godik; D.I. Voroniak; I.V. Kolomoiets; L.О. Trembach; L.Y. Yanovich; О.G. Dubrovin (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Surgical methods of treating portal hypertension (PH) in children make give the opportunity to achieve a lasting effect in the variceal bleeding prevention and reducing pressure in the portal system. The question, regarding the possibility of combining the endoscopic and surgical treatment methods in order to increase the effectiveness of variceal bleeding prophylaxis, remains debatable in children with PH. Aim. To determine the optimal tactics for the prophylactic treatment of variceal bleeding in children with prehepatic PH. Materials and methods. The study design is a retrospective cohort. The data of 84 patients with PH, who were examined and treated during 2016-2019 at the National Children's Specialized Hospital «OKHMATDYT», were analyzed. The study included patients under the age of 18 years with prehepatic PH and the presence of esophageal and stomach varices with the high risk of variceal bleeding. According to the chosen prophylactic method, two groups were formed - surgical and endoscopic treatment. The main study variables were the variceal eradication and the rebreeding number. Results. Data from 21 patients from the endoscopic prophylactic treatment group and 36 from the surgical group were analyzed. A significant difference (p=0.02) of esophageal varices grade was found between the study groups. However, no significant difference between the groups was found for indicators of the gastric varices degree, the red marks presence and the portal gastropathy severity (p>0.05). The complications incidence was significantly higher in the surgical treatment group (p<0.001). Eesophageal varices eradication was achieved in 17 (81%) patients in the endoscopic group and in 15 (41.7%) in the surgical treatment group. It was found that esophageal varices eradication was more commonly achieved in patients with endoscopic treatment (p=0.01). Bleeding after treatment occurred in 4 (19%) patients from the endoscopic group and 14 (38.9%) from the surgical treatment group. No significant difference in the bleeding rates (p=0.15) depending on the treatment type selected was found. Also no significant difference was found for esophageal varices recurrence rates (p=0.35) depending on the selected prophylactic treatment type. Conclusions. Endoscopic prophylactic treatment compared to surgical treatment may be more effective in esophageal varices eradication (p=0.005). Endoscopic treatment has a lower postoperative complications incidence and severity compared to surgical treatment (p<0.001). The optimal prophylactic treatment tactic is a combination of endoscopic and surgical methods to achieve treatment completeness in children with prehepatic PH. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institution. The informed consent of the patient was obtained for conducting the studies.